TERRORIST GROUPS’ LOCALIZATION IN THE POLITICAL SYSTEM - Прошин, Д.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2013)
The article concerns the problem of political localization of such specific subjects of politics as terrorist groups. This problem, which remains under-researched by Ukrainian political science, deserves special attention because of the need to understand as deep as possible the nature of the terrorist threat and effectively respond to it. In the article, the general problems of political localization of terrorist groups are analyzed and rather detailed scheme of possible location of such groups in the political system is outlined.